Mortality among women and men relative to unemployment, part time work, overtime work, and extra work: a study based on data from the Swedish twin registry. Issue 1 (1st January 2001) - Nylén, L; Voss, M; Floderus, B
Abstract : OBJECTIVE: To examine mortality before 70 years of age among women and men relative to unemployment, part time work, overtime work, and extra work. Age, marital status, children, smoking and alcohol habits, use of sleeping pills and tranquilisers, stress, shift work, personality factors, and long lasting or serious illness were taken into account as potential confounding factors. METHODS: The study group comprised a subcohort of the Swedish twin registry, people born in 1926–58. Data were based on a postal questionnaire of 1973 and on information from the Swedish Causes of Death Registry. All subjects reporting a main occupation were selected, 9500 women and 11 132 men, and mortality from all causes during 1973–96 was analysed. The subjects were treated as a sample from the general population regardless of the twinning. RESULTS: Unemployment in 1973 among both women and men showed an association with increased mortality. The adjusted relative risk (RR) (95% confidence interval (95% CI)) was 1.98 (1.16 to 3.38), for women and 1.43 (0.91 to 2.25) for men. For the first 5 years of follow up, a threefold increase in risk was found for men (RR (95% CI) 3.29 (1.33 to 8.17)). The RR declined by time, but remained increased throughout the 24 year study period. In women overtime work of more than 5 hours a week was followed by an increased mortality rate (RR (95% CI) 1.92 (1.13 to 3.25)). A protective effect of moderate overtime work of a maximum 5 hours a week was shown for men (RR (95% CI) 0.58 (0.43 to 0.80)), whereas an increased mortality was indicated for part time work (RR (95% CI) 1.58 (0.91 to 2.77)) and extra work (work outside employment) of more than 5 hours a week (RR (95% CI) 1.29 (0.99 to 1.69)). CONCLUSION: Unemployment and some time aspects of work were associated with subsequent mortality, even when controlling for social, behavioural, work, and health related factors. The idea that losing a job may have less importance for women than for men is not supported by this study.